(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article comes from the experience of a rape trauma and its implications in a personal e social way. In order to investigate the possibilities of intervention in the public sphere by the performative theater, the study was based in an autobiographic approach, analyzing artistic works performed about the theme. Through a philosophical approach, the power structures that maintain the sexual violence were investigated, also considering the subversion that might emerge from its gaps. Thinking of the common sense that circles the theme, the research had as a purpose the proposition of counter-narratives that would trigger off healing processes through the denouncement atmosphere, recurrent in the contemporary scene.